Etika Politik Mohammed Arkoun - Johan Johan; Sutriawal Sutriawal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
As a scientific endeavor, philosophy is divided into several branches, mainly according to the branch discussed. The two main branches of philosophy are theoretical philosophy and practical philosophy. Philosophy thinks about what exists, while practical philosophy interprets how humans imagine what exists. The branch of philosophy that directly interprets human practice is ethics. Ethics deals with human responsibilities and obligations. In relation to politics, political ethics excludes human responsibilities and obligations as humans towards the state, applicable laws, and so on. This article discusses political ethics in Mohammed Arkoun's thought and its relevance to Islamic thought. The data collection method used is documentation study (library research). The findings in this research are that Mohammed Arkoun's political ethics has several important points, namely, 1) criticism of Islamic traditions and modernity, 2) deconstruction of religious political narratives, 3) humanism in politics, 4) pluralism and democracy. Mohammed Arkoun interprets this political ethics as an effort to deconstruct hegemonic political and religious authority.